Obstacles to investment in a context of tax exemption: case of the region LAAYOUNE SAKIA EL HAMRA - ENNAGACH , Rachida; RADI , Bouchra (Revue du contrôle, de la comptabilité et de l’audit, 2022)
In order to improve the investment climate, Morocco has established a new development model for the southern provinces, by committing to a vast reform program. In which Promotion of investment is the crucial axis. However, despite the efforts made and the total exemption of corporate tax in the region of laayoune sakia el hamra, the level of investment is still low due to many constraints on establishment and development. companies. Therefore, the object of this paper, is to study the different obstacles that hinder investment in the region and to study the impact of each obstacle on the level of investment using a sample of 40 companies established in the region. The results revealed a negative impact that differs from one obstacle to another on the decision to invest. At the end of this article, we present a model that associates the decision to invest with the investment obstacles of companies operating in the region.